Technological Mushroom Cultivation as a Means of Food Security In Supporting Natural Disaster Resilience - Kosim; Hakim, Aliefman; Muhajirah; Saputra, Heri Hadi; Niseng, Zakee; Janati; Verawati, Ni Nyoman Sri Putu; Note, Hafsiahnor Pua (Pascasarjana Universitas Mataram, 2025)
West Nusa Tenggara is a region prone to natural disasters, requiring strategies to strengthen food security as part of efforts to build community resilience. One potential alternative is mushroom cultivation based on simple technology. This community service activity aims to introduce and implement a technologically advanced mushroom cultivation model to support food security and disaster resilience in Sembalun Bumbung Village, East Lombok. The method used was participatory training with a learning-by-doing approach, involving the local community in all stages of mushroom cultivation, from media preparation and sensor-based environmental control to harvesting and post-harvest. The results of the activity showed that most participants initially lacked knowledge of mushroom cultivation, but after the training, there was an increase in interest and understanding of the economic and consumption benefits of mushroom cultivation. The implementation of mushroom houses with technology to monitor temperature, humidity, lighting, and biogas utilization was deemed effective and easily adopted by the community. Technologically advanced mushroom cultivation has the potential to become an adaptive and sustainable local food source, thus supporting food security and community resilience in the face of natural disasters.